Pre-Columbian Mesoamerican and Caribbean Ballgames: An Example of Cultural Diffusion - Schultz, Gregory (My University, 2012)
Upon examining the archaeological record and the historical accounts of pre-Columbian cultures in Mesoamerica and in the islands of the Caribbean Sea, one sees evidence of similar ballgames played in both regions. The question then arises, when the geographical and chronological proximity of these cultures is considered, whether these games developed separately, or whether their existence was a product of cultural diffusion. Drawing on insights from archaeology and geography, I argue that there is a connection between Mesoamerican ballgames and those played in the Caribbean. I prove this connection between the two cultures by establishing where and when the ballgame originated, showing when the ballgame arrived in the Caribbean, examining the similarities between the ballgames played in the two regions, and considering whether there is incontrovertible evidence of contact between them. I conclude by addressing what such an intercultural exchange signifies for our understanding of pre-Columbian cultures.
Keywords: Pre-Columbian cultures; Ballgames; Caribbean; Games; Mesoamerica